A Satellite Drift Scan Approach for Establishing the Pointing Model of Radio Telescopes - Ye Yuan; Zhi-Yong Liu; Na Wang; Hao Yan (Advances in Astronomy)
In the era of large satellite constellations, there are more than 1000 satellites in orbit. While the signals from these satellites may pose a risk of radio frequency interference (RFI) to radio telescopes, they also present a potential advantage by serving as high-spatial-density pointing references for radio telescopes. Compared with traditional astronomical radio sources used for radio telescope pointing measurement, these satellites exhibit significantly higher signal-to-noise ratios (SNRs) and more uniform spatial distribution. However, due to the fact that the majority of these satellites are in low Earth orbit (LEO) and move at high velocities, radio telescopes encounter significant challenges in maintaining stable tracking and carrying out cross-scan observations. Therefore, a pointing measurement method utilizing drift-scan toward satellites was proposed. Given the diverse drift directions of satellites, the obtained pointing data encompass a wide range of directions. Therefore, this method is expected to be capable of establishing a pointing model based on scanning data from arbitrary directions. The measurement model and simulation experiments of this method were demonstrated. Furthermore, the feasibility of this method was validated using 25 m Nanshan Radio telescope (NSRT-25m).